The Association Between Ferritin Concentration Within the Blood and Anti-Tissue Transglutaminase (tTG IgA) in Individuals with Celiac Disease - Ahmed A. N Alfahad (Journal of Medical Genetics and Clinical Biology, 2024)
Celiac disease (CD) is a major public health concern across the world. because to the related comorbidities. The purpose of this study was to research the relationship among serum ferritin and anti-tissue transglutaminase (tTG IgA) in celiac disease patients. The research was conducted in Iraq- Muthanna over the course of one year from 2022 to 2023. The study included (5o) (CD) patients and (5o) healthy peoples (control). Patients with chronic disease were excluded. Blood was drawn from (patients and healthy) and tested for ferritin and (tTG IgA). the results showed serum ferritin revealed a negatively correlation with anti-tissue transglutaminase (tTG IgA) (Pearson's regression equal to o.54) in patients with celiac disease . Finally, we can have been concluded from our study the iron storage is represented by ferritin is negatively correlated in patient with celiac disease and anti-tissue transglutaminase (tTG IgA).